Prevalence and materno-fetal outcomes of preeclampsia/eclampsia amongst pregnant women at a teaching hospital in north-central Nigeria: a retrospective cross-sectional study - Godwin O. Akaba; Ubong I. Anyang; Bissallah A. Ekele (BMC, 2021)
Abstract Background Preeclampsia/eclampsia (PE/E) contributes significantly to maternal, perinatal morbidity and mortality in Nigeria. The objectives of the study were to ascertain the prevalence, materno-fetal outcomes and sociodemographic factors associated with PE/E at Nigerian Teaching Hospital from September 2014 to August 2019. Methods This was a retrospective cross-sectional study that analyzed deidentified secondary data of women managed for PE/E at a teaching hospital in north-central, Nigeria. Descriptive statistics were used to determine sample characteristics and study outcome estimates. Bivariate analysis was used to test for associations between sociodemographic factors and PE/E, materno-fetal outcomes while logistic regression analysis was used to test for the magnitude of these associations. The significance level was set at P < 0.05. Results The prevalence of PE/E in this study was 3.60%. Preeclampsia was diagnosed in 3.02% of cases while eclampsia was the diagnosis in 0.58%. Case fatality rate was 3.9% and still birth rate was 10.7%. Majority of women (85.4%) did not have any maternal complication nor unfavorable outcome. Majority (67.7%), of babies weighed less than 2500 g and birth weight was the only sociodemographic factor that was significantly associated with fetal outcome (X2 = 15.6, P < 0.001). Conclusions The prevalence of PE/E in this study is high and is associated with high maternal and perinatal deaths. Majority of the cases of PE/E as well the fatalities occurred in women who had no formal education, unbooked and referred to the teaching hospital with worsening conditions. There is need for explorative research on community factors associated with PE/E and its outcome towards prevention and early management of cases.